Analisis Studi Kelayakan Pendirian Usaha Kersik Mart Melalui BUM Desa Pelangi Kersik Kecamatan Marang Kayu - Juwita Z; Muhammad Fikry Aransyah (Universitas Batanghari, 2023)
One of the ways that supports the village government in realizing the welfare of its people is through economic institutions located in the village, namely the Village-Owned Enterprises (Badan Usaha Milik Desa or BUM Desa). Kersik Mart is one of the planned business units owned by BUM Desa Pelangi Kersik. The purpose of this study is to determine the feasibility of establishing Kersik Mart from the aspects of legal, market, financial, organizational management, and social economic aspects. This research is a qualitative descriptive study using interactive data analysis techniques consisting of data reduction, data presentation, and conclusion drawing. However, in two aspects, namely market and financial aspects, data analysis methods were added, such as market analysis using targeting, segmenting, positioning, and marketing mix analysis. In the financial aspect, the investment feasibility assessment methods used were payback period, net present value, and profitability index. Based on the data analysis, it can be concluded that all five aspects examined are positive, indicating that the establishment of Kersik Mart is feasible. Legal aspects have been planned and the market potential is significant, but more effective marketing strategies are needed. Furthermore, the financial evaluation using PP, NPV, and PI methods resulted in positive values, but attention should be given to investors. The organizational management plan is clear, but competent human resources are still needed. In terms of socio-economic aspects, Kersik Mart can provide positive impacts or benefits for BUM Desa Pelangi and the surrounding community.Top of Form